Developing a Predictive Model of Sense of Coherence in Elderly Women Based on Perceived Social Support with the Mediating Role of Ego Strength - Naeimabadi, Elham; Boostan, Afsaneh; Rezakhani, Simindokht (Psychology of Woman Journal, 2025)
Objective: The present study aimed to develop a predictive model of sense of coherence in elderly women based on perceived social support, with the mediating role of ego strength. Methods and Materials: This applied research employed a correlational design using structural equation modeling for data analysis. The statistical population consisted of all elderly women who visited health centers in Tehran during the first half of 2024. From this population, 220 participants were selected using convenience sampling. Participants completed Antonovsky’s Sense of Coherence Questionnaire, Zimet et al.’s Perceived Social Support Questionnaire, and the Ego Strength Questionnaire developed by Markstrom et al. Data were analyzed using SPSS-24 and AMOS-24. The bootstrap method in the Preacher and Hayes macro was used to assess the mediating variable. Findings: The results indicated that the structural model demonstrated good fit. All direct and indirect path coefficients between perceived social support and sense of coherence, with ego strength as a mediator, were positively significant. Conclusion: It is concluded that elderly women with higher levels of sense of coherence tend to receive greater perceived social support, and their personality functions more effectively due to strong cognitive, emotional, and behavioral ego strength, leading to the utilization of more mature defense mechanisms.